2022
DOI: 10.3389/fendo.2022.932761
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of POMC neurons in LEAP2 regulation of food intake and body weight

Abstract: Liver-expressed antimicrobial peptide 2 (LEAP2) is a newly discovered antagonist of the growth hormone secretagogue receptor (GHSR) and is considered the first endogenous peptide that can antagonize the metabolic actions of ghrelin. The effects of ghrelin administration on feeding behavior, body weight, and energy metabolism involve the activation of orexigenic neurons in the arcuate nucleus (ARC) of the hypothalamus. It is unclear, however, if LEAP2 applied directly to the ARC of the hypothalamus affects thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
12
1
1
Order By: Relevance
“…In fact, in mice fed ad libitum, intracerebroventricular co-administration of LEAP-2 and neuropeptide Y reduced food intake compared with intracerebroventricular neuropeptide Y administration only [ 20 ]. In contrast, LEAP-2 overexpression has been reported to increase pro-opiomelanocortin (POMC) mRNA/protein and intracerebroventricular LEAP-2 administration increased c-fos activity in POMC neurons, thereby highlighting potential anorexigenic effects on neurons to reduce body weight [ 29 ]. This is consistent with work demonstrating through use of a fluorescent-labelled n -terminal LEAP-2 fragment, that LEAP-2 binds to growth hormone secretagogue receptor-1a expressing brain regions (e.g., hypothalamic nuclei, hippocampal dentate gyrus, and medulla) to inhibit food intake [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in mice fed ad libitum, intracerebroventricular co-administration of LEAP-2 and neuropeptide Y reduced food intake compared with intracerebroventricular neuropeptide Y administration only [ 20 ]. In contrast, LEAP-2 overexpression has been reported to increase pro-opiomelanocortin (POMC) mRNA/protein and intracerebroventricular LEAP-2 administration increased c-fos activity in POMC neurons, thereby highlighting potential anorexigenic effects on neurons to reduce body weight [ 29 ]. This is consistent with work demonstrating through use of a fluorescent-labelled n -terminal LEAP-2 fragment, that LEAP-2 binds to growth hormone secretagogue receptor-1a expressing brain regions (e.g., hypothalamic nuclei, hippocampal dentate gyrus, and medulla) to inhibit food intake [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in animals with free access to peanut butter, a strong reduction of LEAP2 mRNA expression could be observed (two-way ANOVA, effect of diet: F (1, 82) =59.62, p<0.0001, interaction effect: F (8, 82) =2.59, p=0.014), and in particular areas associated with reward, such as NAc (p=0.022), VTA (p=0.00068) and LDTg (p<0.0001), and memory, e.g., hippocampus (p=0.0046). Notably, hypothalamus, which is strongly associated with homeostatic eating and energy homeostasis 3, 33, 34 , had the lowest baseline expression, and was not affected by hedonic feeding (p=0.75)…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, in this study, hypothalamic LEAP2 appeared to be the least important for hedonic feeding, considering its low LEAP2 expression and that free hedonic feeding did not alter that expression. A previous study has shown that overexpression of LEAP2 in hypothalamus reduces both chow and high-fat diet consumption 34 , an effect thought to be mediated through arcuate nucleus proopiomelanocortin neurons. Therefore, it appears likely that, although not found here, hypothalamic LEAP2 would affect food intake.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study reported that capsaicin activates TRPV1, which increases glucagon like peptide‐1 (GLP‐1) protein levels and consequently reduces ghrelin (a hunger and energy state‐related hormone) levels in the gut 111 . Arch nucleus contains proopiomelanocortin (ARC POMC) neurons are key regulators of energy homeostasis 134,135 . Many studies have proved that stimulating POMC neurons reduces food intake and restraints obesity 136,137 .…”
Section: Central Regulation Of Obesity By Trpv Ion Channelsmentioning
confidence: 99%
“…111 Arch nucleus contains proopiomelanocortin (ARC POMC) neurons are key regulators of energy homeostasis. 134,135 Many studies have proved that stimulating POMC neurons reduces food intake and restraints obesity. 136,137 It showed activation of TRPV1-like receptor induces the release of anorexigenic α-melanocyte-stimulating hormone from ARC POMC neurons and consequently reduces food intake.…”
Section: Appetite Regulationmentioning
confidence: 99%